The Impact of Environmental, Social and Governance (Esg) Score on Dividend Payment of Large Family Firms: What Is the Role of Financial Constraints? International Evidence - Espinosa-Mendez, C (John Wiley and Sons Ltd, 2024)
This article studies the relationship between environmental, social and governance (ESG) score and dividend payment for 274 large family firms in the period 2015–2021. This research has three contributions to the literature. First, to the best of our knowledge this is the first article to focus on large family firms considering their greater importance in stock ownership around the world. Second, this sample covers both developed and emerging nations. Third, our study not only establishes a connection between ESG (Environmental, Social, and Governance) criteria and dividend payments but also considers how financial constraints moderate the relationship between ESG scores and dividend payments. The results indicate a positive influence of ESG scores on dividend payments. Furthermore, financial constraints of family firms are negatively related to dividend payments. Finally, the moderating effect of financial constraints on the relationship between dividend payment and ESG show that for high levels of financial constraints that dividends are less sensitive to ESG score. The opposite effect is reported when firms show low levels of financial constraints. Practically speaking, the study demonstrates the value of creating a dividend policy that is in line with the ESG score because they are complementary signals. Additionally, it is important to consider financial limitations when planning financial reserves in family firms. This is due to the diminished correlation between ESG score and dividend payments in the presence of financial constraints. © 2023 ERP Environment and John Wiley & Sons Ltd.